1978
DOI: 10.1017/s0094837300006047
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism inNautilusfrom Palau

Abstract: Shells of 375 sexed specimens of Nautilus cf. N. pompilius trapped at 300–700 ft (90–215 m) depth off Mutremdiu Point and Ngemelis Island, Palau, exhibit distinctive dimorphism in shell proportion and overall size. Of 221 mature animals, males have larger shells (mean diameter = 209 mm), a broader aperture (mean maximum width = 99 mm; mean width at apertural salient = 92 mm) and greater weight (mean shell + body weight = 1426 gm). Female shells are smaller (mean diameter = 198 mm), narrower (mean maximum width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 5 publications
2
23
0
Order By: Relevance
“…On the other hand, the results obtained here are consistent with a conclusion that the fished, Philippines populations are significantly different in not only the numbers of nautiluses attracted to the bait each night, but also in terms of the age-class structure of the attracted animals. For example the number of fully mature animals seen at Osprey Reef exceeded 80% [22], and this number is consistent with other studies of age class structure of sampled nautilus populations from Palau in the 1980 s [34], [35]. Our work showed that less than 50% of the observed animals in the Philippines are mature.…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, the results obtained here are consistent with a conclusion that the fished, Philippines populations are significantly different in not only the numbers of nautiluses attracted to the bait each night, but also in terms of the age-class structure of the attracted animals. For example the number of fully mature animals seen at Osprey Reef exceeded 80% [22], and this number is consistent with other studies of age class structure of sampled nautilus populations from Palau in the 1980 s [34], [35]. Our work showed that less than 50% of the observed animals in the Philippines are mature.…”
Section: Resultssupporting
confidence: 91%
“…In Argonauta, which was already mentioned above, the size differences are just as striking as in Ocythoe tuberculata, where the female is 1 m long and so ten times as long as the male (Makowski 1962;Wells 1962Wells , 1966Mangold-Wirz 1963;Westermann 1969a;Mangold-Wirz et al 1969;Roper and Sweeney 1975). By contrast, the male is slightly larger in Recent Nautilida (Willey 1895(Willey , 1902Saunders and Spinosa 1978;Saunders and Ward 1987;Hayasaka et al 1987), but they have a different reproductive strategy. Remarkably, aptychi have been interpreted as protecting the nidamental glands (Keferstein 1866) and Siebold (1848) even suggested that the aptychi were the micromorphic males.…”
Section: Sexing Of Ammonoid Antidimorphsmentioning
confidence: 97%
“…Demographic data include sex and relative maturity of each animal, following established protocols [37, 26]. Sex determination is straightforward in mature animals ( e .…”
Section: Methodsmentioning
confidence: 99%
“…Sex determination is straightforward in mature animals ( e . g ., presence of nidamental glands, lack of a spadix, the shell of females is smaller and the aperture is noticeably compressed [26]). Characteristics of mature animals (maximum growth achieved) include a sinuous aperture (ocular and hyponomic sinuses), thickened shell margin, and a blackened apertural margin in many individuals (but see comments on Osprey Reef data below).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation